Education On Vegetable And Fruit Consumption For Early Childhood In Ranah Singkuang Village - Roziana; Aslis Wirda Hayati; Husnan (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Children’s consumption of vegetables and fruits remains low and often does not meet nutritional recommendations, potentially leading to long-term health problems, including increased risks of chronic diseases such as heart disease and diabetes. Insufficient vegetable intake may also negatively affect eye health and contribute to anemia, resulting in symptoms such as weakness, fatigue, and poor concentration in children. This community service aimed to improve knowledge and awareness regarding fruit and vegetable consumption among early childhood children in Ranah Singkuang Village. The activities were carried out from January to September 2024 at PAUD Ranah Singkuang Village and included educational sessions for children and PAUD teachers focusing on the variety and benefits of fruits and vegetables. The results demonstrated improved knowledge among teachers and young children, as well as positive behavioral changes among parents in providing healthier meals, especially those containing fruits and vegetables. Approximately 95% of students were observed bringing lunches that included fruit and vegetable components following the intervention. Based on these findings, it is recommended that similar educational activities continue to be implemented regularly and that PAUD teachers integrate play-based nutrition learning into daily classroom activities to promote sustainable healthy eating habits among young children.